First description of male of the type species Parosmylus prominens Needham, 1909 (Neuroptera: Osmylidae) from India - Kaur, Simarjit; Pandher, Manpreet Singh; Chandra, Kailash (Zootaxa, 2019)
The male of the type species Parosmylus prominens Needham, 1909 is described for the first time from the material collected from Jammu and Kashmir, Himachal Pradesh, and Uttarakhand, India. The female genitalia are also redescribed based on recently collected material.